The relation between broiler production management with its business analysis in Kediri district, East Java - Rico Anggriawan; David Kurniawan (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2020)
This study was conducted in April to August 2019 to determine the relation between broilers’ production management with its business analysis in Kediri district, East Java. The research using survey methods. The questionnaire was used as a data collection tool, which was carried out by interviews and field observations. Determination of location and respondent uses purposive sampling method and selects 25 farmers. Production management indicators consist of five categories; breed, feeding, housing system, maintenance, and health. Business analysis indicators consist of R/C ratio, Break Event Point (BEP), and Payback Period (PP. Data analysis uses descriptive analysis and statistical analysis of the Structural Equation Modeling (SEM) method using the Partial Least Square (PLS) program. The results showed that farmers had implemented production management well. Broiler partnership farm is a profitable business. The value of Revenue Cost ratio was 1.45 and with the Payback Period for 2.97 years. Production management of broiler farms has a positive and significant effect on its business analysis.